Design of the composition of alkali activated portland cement using mineral additives of technogenic origin - Krivenko, Pavel; Petropavlovskyi, Oleg; Kovalchuk, Oleksandr; Lapovska, Svitlana; Pasko, Anton (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports results of the development of cement compositions and production technology for common cement systems "portland cement clinker – mineral additives – alkaline activator – water-reducing admixture", which contain more than 60 % by weight of mineral additives. The additives have been selected from the group: granulated blast furnace slag, ash from thermal power plants (fly ash and disposed ash) and red mud (waste of alumina production). The relevance of the work relates to the need to improve a number of indicators that limit the widespread application of traditional cements, highly filled with waste (slag portland cement), in particular, early strength and setting terms. We have devised basic principles of the structural arrangement of cement compositions, as well as show the technology of their production. It was established that in terms of the requirements based on acting Ukrainian and European standards, in particular EN 197-1, the designed cements are not inferior to the EN cements, CEM I, CEM II, CEM III, in their characteristics, but even outperform them for strength. The developed cement compositions, which contain the portland clinker in the amount not exceeding 40 % by weight, meet the requirements of the EN standard for the classes of compressive strength (at the age of 28 days) 32,5N − 32,5R; 42,5R − 52,5R. We have investigated the influence of alkaline components on the structure formation processes of artificial stone in the alkaline activated cement at different levels. It was established that an increase in the alkalinity of a cement environment predetermines a decrease in the basicity of the phase composition of neo formations of cement at the micro level, as well as contributes to increasing the total porosity of an artificial stone, which, at the same time, tends to closing and decreases over time.